Effects of autumn and spring primary tillage on soybean yield and 1000-grain weight in the agro-ecological conditions of Serbia - Bajagić Marija; Đukić Vojin; Miladinov Zlatica; Dozet Gordana; Cvijanović Gorica; Miladinović Jegor; Cvijanović Vojin (Agroznanje, 2021)
Soybean yield depends on the selection of cultivars, soil fertility, applied cultivation practices, and agroclimatic conditions over the years. High-quality and timely primary tillage is essential for stable development and high yields of soybean plants. The effect of autumn and spring primary tillage on soybean yield and 1000-grain weight was examined in a three-year study (2013-2015). The trial included cultivars with different maturity periods, developed at the Institute of Field and Vegetable Crops Novi Sad: Valjevka and Galina 0 maturity group, Sava and NS Maximus I maturity group, Rubin and Venera II maturity group. Trial subplots were prepared using different periods of primary tillage, which was conducted in autumn (November, 01-05) and spring (March, 25-31). The highest yields and 1000-grain weight were obtained after autumn primary tillage in all the three study years. Yield decrease by 2.72% to 38.91% and 1000grain weight decrease of 1.33%-11.93% were recorded after spring primary tillage.